Solid Electrolyte Interphase Engineering for Aqueous Aluminum Metal Batteries: A Critical Evaluation. Issue 20 (20th April 2021) - Dong, Tony; Ng, Kok Long; Wang, Yijia; Voznyy, Oleksandr; Azimi, Gisele
Abstract: Rechargeable aqueous aluminum metal batteries (AAMBs) have long been considered unachievable because of the spontaneously formed ionically passivating oxide film and hydrogen evolution reaction on Al. In response, two solid electrolyte interphase (SEI) construction methods, namely, 5 m (mol kg −1 ) Al(OTF)3 ‐based water‐in‐salt electrolyte (Al‐WiSE) and chloroaluminate ionic liquid (IL) pretreatment have been recently reported and seemingly reversible AAMBs were achieved. However, the SEI forming ability of a relatively low concentration Al‐WiSE and the fundamental nature of the IL‐derived SEI remain unclear. Here, with thorough computational, electrochemical, and spectroscopic characterizations, it is revealed that contrary to previous reports, neither of the methods build a stable and effective SEI, and hydrogen evolution reaction remains as the cathodic reaction, without Al deposition. This is the underlying reason for the poor voltage and cyclabilities of current AAMBs. Using insights gained in this work, suggestions for future research is offered on reliable electrolytes and interphases to enable truly reversible AAMBs. Abstract : Two solid electrolyte interphase engineering methods, ionic liquid pretreatment and water‐in salt electrolyte, have seemingly enabled rechargeable aqueous aluminum metal batteries. Their effectiveness is however contentious. Here it is revealed that, contrary to previous reports, no Al deposition occurs, and hydrogen evolution remains as the sole cathodic reaction. Suggestions for the design of more reliable electrolytes and interphases are proposed.